SIMULATION OF HEAT TRANSPORT AT THE COOLING OF THE SUGAR SOLUTION IN A RECUPERATION EXCHANGER - Tomáš Brestovič; Mária Čarnogurská; Miroslav Příhoda; Michal Kubík (Acta Polytechnica, 2015)
The paper describes a mathematical model of the cooling process of a highly concentrated sugar solution in an exchanger with a specifically shaped heat exchanging surface of the cooling panels. An analysis of the individual parts of the stum cooling line is made, dealing with the cooling performance of the cooling panels located in the stum tanks, whose volume is 3230 litres or 1430 litres. One of the monitored parameters is the cooling performance of the JN30 aggregate. The article also deals with an appropriateness of the aggregate for cooling the stum of the total volume 78.21 m3, from the real operation temperature to 0 °C during 48 hours.